2007
DOI: 10.3390/medicina43090095
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in stroke survivors

Abstract: The aim of the study was to compare the quality of life among stroke survivors and healthy controls and to evaluate the influence of age, sex, and social and demographic factors on the quality of life. Contingent and methods. The case group consisted of 508 inhabitants of Kaunas city who were 25–84 years of age and had experienced their first stroke. The control group consisted of age- and sex-stratified randomly selected 508 stroke-free inhabitants of Kaunas city. The quality of life was evaluated using the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
2
2
0
2
Order By: Relevance
“…These results are consistent with the results of previous studies (7,12,13,25,(32)(33)(34)(35), although they include a heterogeneous population and employ HRQOL with a wider variety of scales, including studies conducted on Turkish population. In contrast, a study reports a slight change in HRQOL of patients with stroke (8).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are consistent with the results of previous studies (7,12,13,25,(32)(33)(34)(35), although they include a heterogeneous population and employ HRQOL with a wider variety of scales, including studies conducted on Turkish population. In contrast, a study reports a slight change in HRQOL of patients with stroke (8).…”
Section: Discussionsupporting
confidence: 83%
“…Some studies report different association between the level of education, age, gender, and HRQOL. There are a number of studies that demonstrate that female patients with stroke have lower HRQOL compared with males (10,25,39), although a study has reported no significant differences (33). Kranciukaite et al (33) demonstrated that HRQOL is correlated with education and employment.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to Sociodemographic and quality of life, the result revealed that the university, female, worked and urban patients had high mean score of quality of life with highly statistically differences. These results agreed with Kranciukaite et al, (2007) about "Quality of life in stroke survivors" who demonstrated that HRQOL is correlated with education and employment. These results were disagreed with Gargano and Reeves (2007) who was studying" Sex Differences in Stroke Recovery and Stroke-Specific Quality of Life" found that females had lower SSQOL than males.…”
Section: Discussionsupporting
confidence: 90%
“…2,4,7,8,20 A number of studies demonstrated that female patients with stroke have lower HRQoL compared with males, although one study has reported no significant differences. 4,5,8,20 7,21 The inconsistency between the studies may be related to the design of the studies, patients' characteristics, and using different scales to assess deterioration of HRQoL in stroke patients. In the current study, there was no significant gender difference in terms of HRQoL.…”
Section: Discussionmentioning
confidence: 99%